Teaching evolution thinking Christianly about the teaching of human origins - Hill, Brian (Sydney, NSW Australian Teachers' Christian Fellowship, 1982)
Includes bibliographical references.
Donated by the Australian Teachers' Christian Fellowship, residents of Emmaus Bible College, March 2004.
Keywords: Teaching -- religious aspects -- Christianity; Teaching syllabus -- evolution